Changes in Premature Infant Mercury and Lead Blood Levels after Blood Transfusions - Elabiad, Mohamad T.; Christensen, Michael (American Journal of Perinatology, 2014)
Objective To describe the blood level changes of mercury and lead after packed red blood cell (PRBC) transfusions in ≤ 750 g birth weight infants.Study Design Heavy metal blood levels were measured in infants in PRBC units on 1st, 4th, 5th, and 7th days (D1, D4, D5, and D7) of life and in urine on D1, D4, and D7.Results A total of 10 infants were enrolled with a mean birth weight of 632 ± 72 g. Out of which nine infants received one or more PRBC transfusions, with an average of 2.9 ± 2.5 transfusions per infant. Heavy metals were detected in all the transfusions. The average mercury level was 1.33 µg/L on D1 and 1.66 µg/L on D7, p > 0.05. The average lead level was 0.32 µg/dL on D1 and 0.56 µg/dL on D7, p > 0.05. Urinary mercury excretion increased in infants with no bowel movements. Urinary excretion of lead decreased over time as blood levels increased.Conclusions After receiving blood transfusions, the blood levels of mercury and lead were maintained at the end of the 1st week of life. As there is no evidence of a proportionate increase in excretory amounts of these heavy metals, there is a concern that they are retained and potentially exert toxic effects.
Keywords: blood transfusions; infants; lead; mercury